Theological irradiation Marcos McGrath's Latin American Agenda from the Chile of the 60' (Teología, 2018)
This article presents the figure of Marcos Mc Grath, his participation in the life of the Church in Chile and his life as Bishop in Panama, Father Conciliar and decisive figure for the understanding of the ecclesiological and social view of Medellín. It strengthens the spirit of the Faculty of Theology of the Catholic University of Chile, finding it imperative to achieve the minimum conditions to create an active and vital current of theology where school theologians exchange, expose themselves to the judgment of peers, develop research, question, collaborate closely with the work of the local teaching profession. This research presents us in a theological profile an essential figure for understanding the context and content of Medellín.
Keywords: Seminar; Theology; Investigation; Teología y Vida Magazine; Council